2012
DOI: 10.1038/nn.3165
|View full text |Cite
|
Sign up to set email alerts
|

HMGA regulates the global chromatin state and neurogenic potential in neocortical precursor cells

Abstract: Neural precursor cells (NPCs) in the mouse neocortex generate various neuronal and glial cell types in a developmental stage–dependent manner. Most NPCs lose their neurogenic potential during development, although the underlying mechanisms of this process are not fully understood. We found that the chromatin of mouse NPCs gradually becomes more condensed and less dynamic on a global scale during neocortical development. Furthermore, we found high mobility group A (HMGA) proteins to be essential for the open ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
141
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(145 citation statements)
references
References 46 publications
3
141
1
Order By: Relevance
“…Although H2AX does not affect nucleosome conformation, it has a destabilizing effect that is enhanced by its phosphorylation and results in an impaired linker histone H1 binding [29]. HMGA proteins were shown to dynamically compete with H1 for binding to the linker DNA, thereby loosening the chromatin [30,31]. In addition, displacement of H1 during the initial steps of gene activation has been reported [32].…”
Section: Discussionmentioning
confidence: 99%
“…Although H2AX does not affect nucleosome conformation, it has a destabilizing effect that is enhanced by its phosphorylation and results in an impaired linker histone H1 binding [29]. HMGA proteins were shown to dynamically compete with H1 for binding to the linker DNA, thereby loosening the chromatin [30,31]. In addition, displacement of H1 during the initial steps of gene activation has been reported [32].…”
Section: Discussionmentioning
confidence: 99%
“…By binding to AT-rich DNA and interacting with histone-modifying enzymes and other proteins in enhanceosomes and chromatin, Hmga2 functions as a global epigenetic regulator (22,23). Using a dissociated prostate regeneration approach (24), we examined the contribution of Hmga2-modified stroma to prostate cancer initiation and progression and found that overexpression of stromal Hmga2 was extraordinarily potent and led to the development of multifocal PIN in a paracrine Wnt-dependent manner.…”
Section: Significancementioning
confidence: 99%
“…For example, unique sets of transcription factors are sequentially expressed in different populations of NPCs during brain development, including Pax6, Tbr2 (also known as Eomes) and Sox2 (Englund et al, 2005;Graham et al, 2003;Sessa et al, 2008). Epigenetic regulators modulate chromatin states to control NPC self-renewal and neurogenic potentials in a developmental stage-dependent manner (Kishi et al, 2012;Lim et al, 2009;Nishino et al, 2008). Although these studies have provided significant insights into the highly coordinated gene expression program at transcriptional levels for NPC behavior control, little is known about gene regulation at post-transcriptional levels for NPC self-renewal and brain development.…”
Section: Introductionmentioning
confidence: 99%